A funny thing happened on the way to the future : twists and turns and lessons learned - Fox, Michael J., 1961- (Hyperion, 2010)
This optimistic volume by the author of the bestselling "Always Looking Up" inspires and motivates readers to work hard, achieve the most they can, and maximize their abilities.